How Russia’s wars affected Türkiye-US relations between 2014-2022?: An American perspective - ÇETİNOĞLU HARUNOĞLU, AYŞE NUR (My University, 2023)
One of the most challenging international developments of the President Obama’s term was the annexation of Crimea by Russia in 2014. Interestingly his vicePresident Biden, who became the President of the US in January 2021, faced even a greater challenge in February 2022 when Russia invaded Ukraine. While the security of the Black Sea came to the forefront with the outbreak of a war in Ukraine, relations between Turkey and the US have been also re-assessed in this tumultuous period. Victoria Nuland, the US Under Secretary of State for Political Affairs, said in a testimony she gave in the Senate Foreign Relations Committee in March 2022 that “Turkey has taken some very strong moves since the conflict began under the Montreux Convention to deny warship access”. Meanwhile, the Biden administration recently announced the launch of a “strategic mechanism” with Turkey, a structural platform to discuss all matters facilitating practical bilateral cooperation. These developments were defined by some political as well as academic circles, as the appreciation of Turkish efforts in the Black Sea by the US, thus the amelioration of bilateral ties after turbulent crises faced in 2010s. Unlike the pieces analyzing the Turkish perceptions on Russia, Ukraine and Black Sea, this paper seeks to understand the American perspective on the implications of Russia’s wars in Ukraine on Turkey-US relations, by relying on the hearings held in the Senate Foreign Relations Committee. In other words, the papers aims to evaluate discussions on Turkey, held in the Senate’s related committee to understand how Senate perceives the connection between Russia’s wars in Ukraine and Turkey-US relations between 2014-2022.
Keywords: Turkey-US Relations; Russia; Ukraine; US Senate